EVALUASI BIAYA UNTUK PENETAPAN TARIF KELAS RAWAT INAP PADA RUMAH SAKIT SWASTA (Studi Kasus pada Rumah Sakit Panti Nirmala Malang) - Josi Eka Ariyani; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACT The purpose of this study to evaluate the cost of tariffs inpatient hospital Panti Nirmala Malang. Type of research is descriptive. Data source used in this study are primary data and secondary data, while the method of data collection was done by using the of documentation. Methods of data analysis used in this research is quantitative descriptive method. This study has shown that there is a difference between Panti Nirmala Malang hospital rates with rates from the analysis that has been done. It is likely to be due to underestimation of the components associated with hospitalization or the possibility that the hospital has set calculation Panti Nirmala Malang hospitalization rates but still not right, so it can be the difference or deviation occurs in the inpatient unit at hospital Panti Nirmala Malang.Keyword : Class Rates Of Hospitalization